Imagining the Arabs - Aaron W. Hughes (International Institute of Islamic Thought, 2017)
I often tell graduate students that there are three constituent parts to cuttingedge scholarship: (1) the requisite linguistic and historical training, (2) creativity and imagination, and (3) a bold vision that desires to take inherited ideas and subject them to new and rigorous analyses. Very few can do this, but those who can end up radically transforming our understanding of a topic. I am happy to say that Peter Webb has met all three of these criteria in his wonderful and thought-provoking Imagining the Arabs. He has presented us with a paradigm-shifting study, and all subsequent work on the topic will have to wrestle with his monograph. Webb’s goal is sufficiently bold: to rethink the Arabs – who they were, what they believed, where they came from, and how they were imagined by various elites in the early Islamic period. Received opinion has, like so much in early Islamic history, simply repeated what the earliest sources (paradoxically from later periods) tell us. The assumption is that such sources must be true because there is no reason why they should not be. Why, for example, should they cultivate untruths or spread ideological rumors? Instead of adopting, as so many do, a posture of gullibility, Webb prefers to see such texts as engaged in the dual processes of ethnogenesis and mythopoesis. Tradition assumes that the Arabs were a homogenous group of of Bedouins that have inhabited the Arabian Peninsula since Antiquity. This would be akin, as Webb informs us, of assuming that all of the first nations in North America were essentially the same with respect to religion, culture, and ethnicity, and something that ignores that the aforementioned terms have distinct lineages in modern political and nationalist thought. Then in the seventh century CE, so the story continues, these Arabs adopted a new faith, to wit, Islam, and rapidly conquered the Middle East and beyond. Study after study has simply assumed that these “Arabs,” while sensitive to poetry, represented a form of militarized ...